Pengembangan Penguasaan Kemampuan Berbahasa dan Berbicara pada Anak Tunarungu di SLB Negeri Widi Asih Padaherang - Niki Nurul Puadah; Komariah Komariah; Santi Nurandiyani; Aneu Siti Rohmah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
This study aims to find out how to develop masteo•' of language and speaking skills in deaf children at SLB Negeri Widi Asih Padaherang. This study uses a qualitative method. Data collection techniques were carried out through observation, interviews and documentation studies. The results of the study found that in fact language skills in understanding language (receptive language) must first be developed before developing speech skills. This repressive language is a medium for conveying messages in the form of spoken language (expressive language), namely the development of language and speaking skills which are a useful unit in communication.